Dinamika fertilitas dan prevalensi kontrasepsi di Indonesia - Umi Listyaningsih; Sonyaruri Satiti (Research Centre for Population, National Research and Innovation Agency (BRIN), 2021)
The fertility dynamics are related to the direction of population policies and socio-economic conditions of the community. From the 1970s to 1990, Soeharto had succeeded in reducing fertility rates. Unfortunately, population control had weakened in 2000 when the government adopted regional autonomy. Consequently, population control was no longer a priority due to the merger of institutions with the full authority of population and family planning. In addition, improving the socio-economic conditions of society poses challenges to population control efforts. This paper aims to analyze fertility and contraceptive prevalence rate trend in Indonesia based on the 2017 Indonesia Demographic and Health Survey data. The data were analyzed using inferential statistics. The results indicate socio-economic conditions affect people’s mindset in deciding the use of contraception and pregnancy. People are aware of birth control but tend not to use modern contraception and move to traditional contraception. The socio-economic improvement of women, which causes negative child value, is sufficiently a sufficient condition to maintain or reduce fertility. Other factors such as improvement of maternal education, maternal participation in work, and increased family welfare that is important to keep fertility at a low level.